Literacy Development in Serui, Papua: Challenges, Educational Practices, and Community-Based Strategies in Remote Primary Education - Yenniwati Sinaga; Lirhan Lirhan; Susanti F Susanti F; Rafli Bondi (PT. Anagata Sembagi Education, 2026)
This study aims to examine literacy development in remote primary schools in Serui, Papua, by analyzing the interaction between structural constraints, pedagogical practices, and community engagement. Unlike previous studies that tend to isolate these factors, this research positions literacy as both a cognitive skill and a sociocultural practice, highlighting the need for an integrated analytical framework in multilingual and geographically isolated contexts. This study employed a convergent mixed-method multiple-case study design, in which qualitative and quantitative data were collected concurrently and integrated during analysis. The study involved six primary schools, 12 teachers, 6 principals, 48 students, and 24 parents selected through purposive sampling based on their active involvement in literacy practices. Data were obtained through classroom observations, semi-structured interviews, document analysis, and Oral Reading Fluency (ORF) assessments. Qualitative data were analyzed thematically, while quantitative data were analyzed descriptively, followed by data triangulation to ensure validity. The findings indicate that literacy outcomes are shaped by the interplay of structural limitations, multilingual instructional challenges, and community participation. Schools implementing culturally responsive pedagogy and community-based literacy programs showed higher reading performance (mean 66 WPM vs. 57 WPM). The integration of mother-tongue scaffolding and local storytelling significantly enhanced student engagement and comprehension. Based on these findings, this study proposes the Community-Integrated Literacy Framework (CILF) as a context-sensitive model for improving literacy in remote and multilingual settings.